(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2020)
The tomato crop is confronted to numerous soilborne pathogens, including Ralstonia solanacearum, which considerably limits its production. In order to control this bacterium, a biological control approach has been considered by evaluating the efficacy of the NECO biopesticide against this bacteriosis. In vitro confrontations were carried out using a range of five concentrations of the biopesticide. In vivo, NECO solutions of 5 and 10 mL/L were incorporated into soil previously infested with R. solanacearum before transplanting tomato plants. Zones of bacterial growth inhibition were observed after the application of the NECO biopesticide. Results showed that the 20 mL/L concentration resulted in a higher inhibition rate. The biopesticide at the 10 mL/L concentration significantly reduced the incidence of bacterial wilt (54.05%) under in vivo conditions. The NECO biopesticide could be used as a control agent for Ralstonia solanacearum.